2013
DOI: 10.1111/tmi.12100
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of placenta praevia by world region: a systematic review and meta‐analysis

Abstract: Abstractobjectives (i) To estimate the prevalence burden of placenta praevia in each world region, and (ii) to investigate potential sources of heterogeneity.methods Systematic review of the literature and random-effects meta-analysis. Potential sources of heterogeneity were investigated using meta-regression.results The overall prevalence of placenta praevia was 5.2 per 1000 pregnancies (95% CI: 4.5-5.9). However, there was evidence of regional variation (P = 0.0001); prevalence was highest among Asian studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
3
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(133 citation statements)
references
References 53 publications
3
112
3
4
Order By: Relevance
“…14 Cresswell JA et al In a systematic review and meta-analysis found a very high level of heterogeneity and regional variations in the incidence of placenta praevia; the highest was in the Asian countries. 15 This finding is supportive for our finding which was different from finding in other regions of the world and nearly similar to others. There may be undiscovered factors that lead to this variation which requires further studies.…”
Section: Discussionsupporting
confidence: 89%
“…14 Cresswell JA et al In a systematic review and meta-analysis found a very high level of heterogeneity and regional variations in the incidence of placenta praevia; the highest was in the Asian countries. 15 This finding is supportive for our finding which was different from finding in other regions of the world and nearly similar to others. There may be undiscovered factors that lead to this variation which requires further studies.…”
Section: Discussionsupporting
confidence: 89%
“…Placental abnormality was reported in 21 (11.2%) pregnancies, with placenta previa being the most commonly reported abnormality (Table 2). The rate of placenta previa within our cohort was 3.2%, which is significantly higher than the North American population prevalence of 0.29% (p<0.001) (15). Of the 6 patients with placenta previa, 2 (33.3%) were diagnosed in the first trimester, 1 (16.7%) in the second trimester, 1 (16.7%) in the third trimester, and 2 (33.3%) were unknown.…”
Section: Resultscontrasting
confidence: 67%
“…2,3 The incidence appears to have increased in relationship to the increasing rate of cesarean deliveries. Indeed, there is a dose-response relationship between the number of previous cesarean deliveries and subsequent placenta previa.…”
Section: Placenta Previa Backgroundmentioning
confidence: 94%